2018
DOI: 10.1016/j.currproblcancer.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Advanced imaging modalities to detect cardiotoxicity

Abstract: Recent advances in cancer treatments have significantly improved survival rates, reemphasizing the focus on reducing the potential complications associated with some therapies. Cardiovascular disease associated with chemotherapies is a major cause of morbidity and mortality in cancer survivors. Early detection of cardiotoxicity improves cardiac outcomes among cancer patients. The review will focus on imaging modalities used to assess cardiotoxicity - the cardiovascular consequences of chemotherapies. The revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 75 publications
0
15
0
2
Order By: Relevance
“…Specifically, longitudinal evaluation of dose‐dependent RT‐induced damage requires registering MR data onto planning CTs from which quantitative dosimetry maps are formed. Notably, cardiac magnetic resonance (CMR) is an established technique to assess the function and structure of the heart (e.g., ventricular volumes, ejection fraction, left ventricular strains, LGE, and tissue characterization using T1/T2 mapping), 32,33 particularly for evaluating chemotherapy and radiotherapy‐induced CVT in long‐term thoracic cancer survivors (e.g., lung, breast, or lymphatic tissue) 33–36 . For example, prior studies have shown that CMR can detect significant T1 changes, declining ejection fraction, abnormalities in myocardial strain, and left atrial‐scar enhanced volume following RT 37–40 .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, longitudinal evaluation of dose‐dependent RT‐induced damage requires registering MR data onto planning CTs from which quantitative dosimetry maps are formed. Notably, cardiac magnetic resonance (CMR) is an established technique to assess the function and structure of the heart (e.g., ventricular volumes, ejection fraction, left ventricular strains, LGE, and tissue characterization using T1/T2 mapping), 32,33 particularly for evaluating chemotherapy and radiotherapy‐induced CVT in long‐term thoracic cancer survivors (e.g., lung, breast, or lymphatic tissue) 33–36 . For example, prior studies have shown that CMR can detect significant T1 changes, declining ejection fraction, abnormalities in myocardial strain, and left atrial‐scar enhanced volume following RT 37–40 .…”
Section: Discussionmentioning
confidence: 99%
“…In order to illustrate the challenges of deploying imaging as a biomarker of safety, consider the risks of cardiotoxicity in cancer therapy. 175 This includes any structural or functional heart injury related to cancer treatment. Injury most commonly involves the myocardium leading to heart failure (HF) but can also include the pericardium, valves or coronary arteries.…”
Section: Timothy J Mccarthy Phd Pfizer Usamentioning
confidence: 99%
“…ECHO allows clinicians to assess the LV volume, dimensions, and overall function. Furthermore, the ECHO allows for visualization of any valvular or pericardial pathologies [ 74 ]. Due to the increased prevalence of cardiac complications with chemotherapy in the pediatric population, monitoring throughout the course of chemotherapy treatment is essential and can be useful in mitigating long-term cardiovascular toxicity.…”
Section: Reviewmentioning
confidence: 99%